Comparison between a handheld ultrasound device and a traditional ultrasound for performing transcranial sonography in patients with Parkinson's disease. Issue 2 (27th January 2023) - Paes, Maria A. S.; Nicaretta, Denise H.; Alvarenga, Regina M. P.; Rosso, Ana L. Z.; Brisson, Rodrigo T.; Fernandes, Rita C.L.
Abstract: Objective: The aim of this study is to compare a portable ultrasound (US) device and a traditional US for performing transcranial ultrasonography (CCT) in patients with Parkinson's disease (PD). Methods: This is a cross‐sectional, observational, and analytical study. The study recruited a total of 129 individuals from two public hospitals in the city of Rio de Janeiro in a prospective and non‐randomized manner between September 2019 and July 2021 as follows: group A with 31 patients with PD, group B with 65 patients with PD, and group C with 64 healthy individuals. Group A was used to collect data to establish the agreement analysis of the TCS measurements between the two devices. Groups B and C provided data for constructing the receiver operating characteristic curve for the handheld US. The subjects underwent the assessment of the transtemporal bone window (TW) quality, the mesencephalon area, the size of the third ventricle, and the substantia nigra (SN) hyperechogenicity area. Results: There was a good agreement between the methods regarding the quality of the TW–Kappa concordance coefficient of 100% for the right TW and 83% for the left, the midbrain area—intraclass correlation coefficient (ICC) of 69%, the SN area ICC = 90% for the right SN and 93% for the left and the size of the third ventricle ICC = 96%. The cutoff point for the SN echogenic area in the handheld US was 0.20 cm 2 . Conclusions: The handheld US is a viable imaging method for performing TCS because it shows good agreement with the measurements performed with traditional equipment, and the measurement of SN echogenic area for PD diagnosis presents good sensitivity and specificity. Abstract : Graph 1. The receiver operating characteristic (ROC) curve. The area under the curve is 0.91 with a confidence interval (CI) of 95%: 0.84–0.97. The best substantia nigra cutoff value was 0.20 cm 2 . Sensitivity = 0.98 and specificity = 0.87.